Characteristics of headache and relationship to acute mountain sickness at 4559 meters - Schneider, Michael; Bärtsch, Peter (High altitude medicine & biology, 2018)
The goals of this study were to characterize headache at high altitude in relation to the severity of acute mountain sickness (AMS), to investigate whether a history of migraine or nonmigrainous headache at low altitude is a risk factor for AMS and to estimate its effect size in relation to established major risk factors. We performed a secondary, extended analysis of data obtained from 1320 mountaineers staying overnight at the Capanna Margherita (4559 m). Headache at low and high altitude was classified according to the criteria of the International Headache Society. About 45% of the mountaineers suffered from headache in the evening of the arrival day at 4559 m. In those with headache, tension type headache decreased from 62% to 29% and 13% with no AMS (AMS-C <0.70), moderate AMS, and more severe AMS (AMS-C ≥1.5), while headache fulfilling the criteria of migraine increased correspondingly from 14% to 34% and 69%. A history of migraine or any type of headache at low altitude is a minor predictor of AMS that does not significantly contribute to AMS risk in a multivariate analysis including the major risk factors such as history of AMS, rate of ascent, and degree of preacclimatization in this population of alpine mountaineers. The association between more severe AMS and migrainous headache may be due to common nonspecific symptoms but a common underlying pathophysiology of AMS and migraine cannot be excluded. Despite this association a history of migraine or other headache at low altitude is not a major risk factor for AMS.
Gesehen am 09.07.2019